Positive electrode material, electrochemical device, and electronic device
By regulating the internal pore structure of the positive electrode material particles, the poor mechanical properties and cracks of ternary polycrystalline materials are solved, and the circulation performance and high-temperature storage performance of lithium-ion batteries are improved.
Patent Information
- Application Number
- CN202380038396.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-10-20
AI Technical Summary
Triple polycrystalline materials have poor mechanical properties in lithium-ion batteries and are prone to particle cracks, resulting in worsening of battery gas production and circulation life, and there is a risk of cracks during the cold pressing of the extreme sheet.
By regulating the pore structure distribution inside the positive electrode material particles, it is ensured that the difference in the void ratio between the first and second regions is between 5% and 30%, the length of the hole does not exceed 5μm, the width does not exceed 1.5μm, and the length direction and diameter of the holes The holes are distributed radially at intervals in a uniform direction.
It effectively reduces the stress influence of charge and discharge cycles and cold pressing on particles, improves the circulation performance and high-temperature storage performance of electrochemical devices, and improves the energy density and structural stability of the battery.
Smart Images

Figure CN119156720A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to positive electrode materials and electrochemical devices and electronic devices comprising the positive electrode materials. Background Art
[0002] With the increasing depletion of fossil energy, people are paying more and more attention to the demand for clean energy, and lithium-ion batteries play an important role in this. Ternary materials have been widely used due to their advantages of low cost and high energy density, especially in the field of electric vehicles. However, the mechanical properties of ternary polycrystalline materials themselves are poor and cracks between particles are prone to occur during the cyclic charge and discharge process. These cracks will aggravate the side reactions between the electrolyte and the positive electrode material, resulting in battery gas production and deterioration of cycle life. Moreover, there is also a risk of causing cracks in polycrystalline material particles during the cold pressing process of the pole piece. Summary of the invention
[0003] In view of the above-mentioned problems existing in the prior art, the present application proposes a positive electrode material, an electrochemical device and an electronic device, which solves the problem that the positive electrode material has poor mechanical properties and is prone to cracks during the cycle process by regulating the distribution of the pore structure inside the positive electrode material particles.
[0004] In a first aspect, the present application provides a positive electrode material, wherein the cross-section of the positive electrode material particle includes a first region and a second region; wherein, with the midpoint of the longest diameter in the cross-section as the center, a line connecting the center to any point on the surface of the positive electrode material particle in the cross-section is a first line, and there is a first dividing point on the first line, and the distance from the center to the first dividing point is 3 / 5 of the length of the first line where the first dividing point is located, and the first region is the region enclosed by the first dividing point; the second region is the region outside the first region in the cross-section; the porosity of the first region is Vc1, and the porosity of the second region is Vc2, satisfying: 5%≤Vc2-Vc1≤30%.
[0005] In some embodiments, the positive electrode material satisfies: 7%≤Vc2-Vc1≤18%.
[0006] In some embodiments, the positive electrode material satisfies: 3%≤Vc1≤30%.
[0007] In some embodiments, the positive electrode material satisfies: 10%≤Vc2≤35%.
[0008] In some embodiments, the second region includes a hole, and the length of the hole is L, L≤5 μm.
[0009] In some embodiments, the width of the hole is d, and d≤1.5 μm.
[0010] In some embodiments, a length direction of the hole is consistent with a radial direction of the second region.
[0011] In some embodiments, the holes are radially spaced apart.
[0012] In some embodiments, the positive electrode material is assembled with lithium metal into a button battery, and when the button battery is charged and discharged at a current of 0.1C in the voltage range of 2.8V to 4.5V, the obtained capacity-voltage differential dQ / dV curve has a first oxidation peak and a first reduction peak in the range of 4.2V to 4.5V.
[0013] In some embodiments, the peak voltage of the first oxidation peak is Vo1, the peak voltage of the first reduction peak is Vr1, and |Vo1-Vr1|≤0.2V.
[0014] In some embodiments, the capacity-voltage differential dQ / dV curve has a second oxidation peak and a second reduction peak in the range of 3.6V to 4.0V, the peak voltage of the second oxidation peak is Vo2, the peak voltage of the second reduction peak is Vr2, and |Vo2-Vr2|≤0.3V.
[0015] In some embodiments, based on the mass of the positive electrode material, the peak height of the first oxidation peak is in the range of 2000 mAh / g / V to 4000 mAh / g / V.
[0016] In some embodiments, based on the mass of the positive electrode material, the absolute value of the peak height of the first reduction peak is in the range of 2000 mAh / g / V to 4000 mAh / g / V.
[0017] In some embodiments, when the button cell is charged and discharged at a current of 0.1C in a voltage range of 2.8V to 4.5V, a discharge curve in the obtained voltage-capacity curve has a platform in the range of 4.2V to 4.5V.
[0018] In some embodiments, when the button battery is charged and discharged at a current of 0.1C in a voltage range of 2.8V to 4.5V, the capacity of the discharge curve in the obtained voltage-capacity curve in the range of 4.2V to 4.5V is Q1, and the capacity of the discharge curve in the range of 2.8V to 4.5V is Qt, satisfying: 0.2≤Q1 / Qt≤0.35.
[0019] In some embodiments, the positive electrode material includes a lithium transition metal oxide, which includes a T element and an optional M element, wherein the T element includes at least one of Ni, Co, or Mn, and the M element includes at least one of K, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, B, Si, P, S, Sc, Ti, V, Cr, Fe, Cu, Zn, Ga, or Ge.
[0020] In some embodiments, based on the total molar amount of the T element in the lithium transition metal oxide, the molar percentage of the Ni element is 30% to 70%.
[0021] In some embodiments, based on the total molar amount of T element in the lithium transition metal oxide, the molar percentage of Mn element is less than or equal to 70%; and / or, based on the total molar amount of T element in the lithium transition metal oxide, the molar percentage of Co element is less than or equal to 50%.
[0022] In some embodiments, based on the total molar amount of the T element and the M element in the lithium transition metal oxide, the molar percentage of the T element is 90% to 100%, and the molar percentage of the M element is 0% to 10%.
[0023] In some embodiments, in the lithium transition metal oxide, the ratio of the molar amount of the Li element to the total molar amount of the T element and the M element is 0.5 to 1.1.
[0024] In some embodiments, the lithium transition metal oxide further includes a Na element, and the molar percentage of the Na element is 0.1% to 20% based on the total molar amount of the T element and the M element in the lithium transition metal oxide.
[0025] In some embodiments, the lithium transition metal oxide further includes an R element, wherein the R element includes at least one of F, Cl, Br, I or N, and the molar percentage of the R element is 0.1% to 10% based on the total molar amount of the T element and the M element in the lithium transition metal oxide.
[0026] In some embodiments, the lithium transition metal oxide has a layered crystal structure.
[0027] In some embodiments, the lithium transition metal oxide includes Li x1 Na x2 Ni y1 Mn y2 Co y3 M z1 O 2±m Rm , 0.5≤x1≤1.1, 0.001≤x2≤0.2, 0.3≤y1≤0.7, 0≤y2≤0.7, 0≤y3≤0.5, 0≤z1≤0.1, 0≤m≤0.1, wherein the R element includes at least one of F, Cl, Br, I or N.
[0028] In some embodiments, the X-ray diffraction pattern of the positive electrode material has diffraction peaks in the ranges of 16° to 20°, 34° to 38°, and 42° to 46°.
[0029] In a second aspect, the present application further provides an electrochemical device, which includes a positive electrode, wherein the positive electrode includes a positive electrode active material layer, wherein the positive electrode active material layer includes the positive electrode material of the first aspect.
[0030] In a third aspect, the present application provides an electronic device comprising the electrochemical device of the second aspect.
[0031] Beneficial effect: This application can effectively reduce the influence of cold pressing of the electrode and charge-discharge cycle on the stress between polycrystalline particles by regulating the distribution of the pore structure inside the positive electrode material particles, thereby improving the problem of particle cracks caused by cold pressing and cycling, and further improving the cycle performance and high-temperature storage performance of the electrochemical device. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a cross-sectional SEM photograph of the positive electrode material particles of Example 1.
[0033] Figure 2 XRD patterns of the positive electrode materials of Comparative Example 1 and Example 6.
[0034] Figure 3 The voltage-capacity curves of button batteries of Comparative Example 1 and Example 6 are shown.
[0035] Figure 4 The capacity-voltage differential dQ / dV curves of the button-type batteries of Comparative Example 1 and Example 6 are shown. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.
[0037] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0038] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0039] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0040] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0041] In the first aspect, the present application provides a positive electrode material, wherein the cross section of the positive electrode material particle includes a first region and a second region; wherein, with the midpoint of the longest diameter in the cross section as the center, the line connecting the center to any point on the surface of the positive electrode material particle in the cross section is the first line, the first line has a first dividing point, the distance from the center to the first dividing point is 3 / 5 of the length of the first line where the first dividing point is located, the first region is the region surrounded by the first dividing point; the second region is the region outside the first region in the cross section; the porosity of the first region is Vc1, and the porosity of the second region is Vc2, satisfying: 5%≤Vc2-Vc1≤30%. Positive electrode material particles that meet the above conditions can effectively alleviate the effects of cold pressing of the pole piece and charge-discharge cycles on the stress between particles, improve the problem of particle cracks caused by cold pressing and charge-discharge cycles, and further improve the cycle performance and high-temperature storage performance of the electrochemical device.
[0042] In some embodiments, Vc2-Vc1 may be 5%, 7%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or a range consisting of any two of these values. In some embodiments, the positive electrode material satisfies: 7%≤Vc2-Vc1≤18%.
[0043] In some embodiments, the positive electrode material satisfies: 3% ≤ Vc1 ≤ 30%. In some embodiments, Vc1 can be 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, or a range consisting of any two of these values. In some embodiments, the positive electrode material satisfies: 10% ≤ Vc2 ≤ 35%. In some embodiments, Vc2 can be 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, or a range consisting of any two of these values. When the porosity is too high, too many voids will make it difficult for electrons to flow in the material, making the electronic conductivity of the positive electrode material particles worse, thereby reducing the conductivity of the material. In addition, too high a porosity will increase the path of ion transmission, resulting in a slower diffusion rate of ions in the material, reducing the charge and discharge rate of the battery. Inevitably, too high a porosity will also lead to unstable structure of the material, which is prone to expansion, contraction or structural damage, affecting the life and safety of the battery. On the other hand, when the porosity is too low, it will limit the free diffusion of ions, making it difficult for ions to be efficiently transmitted in the material, reducing the charge and discharge performance of the battery. In addition, the polycrystalline positive electrode material will expand in volume during the charging process. If the voids are too small to accommodate the expanded material, it may cause the material to rupture or the battery to fail. Therefore, the porosity needs to be limited to a reasonable range.
[0044] In some embodiments, the second region includes a hole, and the length of the hole is L, L≤5μm. In some embodiments, L can be 0.2μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, or a range consisting of any two of these values. In some embodiments, the width of the hole is d, d≤1.5μm. In some embodiments, d can be 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, or a range consisting of any two of these values. In order to obtain good electrochemical performance, the pores of the positive electrode material are controlled within the above-mentioned appropriate range, which can not only ensure good transmission of electrons and ions, but also better accommodate the volume changes of the material.
[0045] In some embodiments, the length direction of the hole is consistent with the radial direction of the second region. In some embodiments, the holes are radially spaced. The holes arranged in the above manner can better disperse the stress during cold pressing and cycling, reduce the particle crack phenomenon during cold pressing and cycling, and thus improve the cycling performance and high temperature storage performance of the electrochemical device.
[0046] In some embodiments, the positive electrode material is assembled with lithium metal into a button battery, and when the button battery is charged and discharged at a current of 0.1C in the voltage range of 2.8V to 4.5V, the obtained capacity-voltage differential dQ / dV curve has a first oxidation peak and a first reduction peak in the range of 4.2V to 4.5V.
[0047] In some embodiments, the peak voltage of the first oxidation peak is Vo1, the peak voltage of the first reduction peak is Vr1, and |Vo1-Vr1|≤0.2V. This indicates that the positive electrode material has a reversible charge and discharge capacity in the high voltage range of 4.2V to 4.5V, so that the positive electrode material has a high energy density and good structural stability. In some embodiments, |Vo1-Vr1| can be 0.2V, 0.18V, 0.16V, 0.14V, 0.12V, 0.1V, 0.08V, 0.06V, 0.04V, 0.02V, 0.01V, or a range consisting of any two of these values.
[0048] In some embodiments, when the button cell is charged and discharged at a current of 0.1C in a voltage range of 2.8V to 4.5V, the capacity-voltage differential dQ / dV curve has a second oxidation peak and a second reduction peak in a range of 3.6V to 4.0V. The peak voltage of the second oxidation peak is Vo2, the peak voltage of the second reduction peak is Vr2, and |Vo2-Vr2|≤0.3V. In some embodiments, |Vo1-Vr1| can be 0.3V, 0.28V, 0.26V, 0.24V, 0.22V, 0.2V, 0.18V, 0.16V, 0.14V, 0.12V, 0.1V, 0.08V, 0.06V, 0.04V, 0.02V, 0.01V, or a range consisting of any two of these values.
[0049] In some embodiments, based on the mass of the positive electrode material, the peak height of the first oxidation peak is in the range of 2000 mAh / g / V to 4000 mAh / g / V, indicating that the positive electrode material can have a higher charging capacity in the high voltage range of 4.2 V to 4.5 V, thereby improving the charging capacity of the electrochemical device.
[0050] In some embodiments, based on the mass of the positive electrode material, the absolute value of the peak height of the first reduction peak is in the range of 2000 mAh / g / V to 4000 mAh / g / V, indicating that the positive electrode material can have a higher reversible discharge capacity in the high voltage range of 4.2 V to 4.5 V, thereby improving the energy density of the electrochemical device.
[0051] In some embodiments, when the button cell is charged and discharged at a current of 0.1C in a voltage range of 2.8V to 4.5V, the discharge curve in the obtained voltage capacity curve has a platform in the range of 4.2V to 4.5V, indicating that the positive electrode material can have a reversible discharge capacity in the high voltage range of 4.2V to 4.5V.
[0052] In some embodiments, when the button cell is charged and discharged at a current of 0.1C in a voltage range of 2.8V to 4.5V, the capacity of the discharge curve in the voltage capacity curve obtained in the range of 4.2V to 4.5V is Q1, and the capacity of the discharge curve in the range of 2.8V to 4.5V is Qt, satisfying: 0.2≤Q1 / Qt≤0.35. At this time, the capacity of the positive electrode material in the high voltage range of 4.2V to 4.5V is higher, so that the positive electrode material has a higher energy density.
[0053] In some embodiments, the positive electrode material includes a lithium transition metal oxide, which includes a T element and an optional M element, wherein the T element includes at least one of Ni, Co, or Mn, and the M element includes at least one of K, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, B, Si, P, S, Sc, Ti, V, Cr, Fe, Cu, Zn, Ga, or Ge.
[0054] In some embodiments, based on the total molar amount of T element in the lithium transition metal oxide, the molar percentage of Ni element is 30% to 70%, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or a range consisting of any two of these values.
[0055] In some embodiments, based on the total molar amount of T element in the lithium transition metal oxide, the molar percentage of Mn element is less than or equal to 70%, for example, 0.5%, 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70% or a range consisting of any two of these values.
[0056] In some embodiments, based on the total molar amount of the T element, the molar percentage of the Co element is less than or equal to 50%, for example, 0.5%, 1%, 5%, 10%, 20%, 30%, 40%, 50%, or a range consisting of any two of these values.
[0057] In some embodiments, based on the total molar amount of T element and M element in the lithium transition metal oxide, the molar percentage of the T element is 90% to 100%, for example, 90%, 92%, 95%, 96%, 98%, 99%, 100% or a range consisting of any two of these values; the molar percentage of the M element is 0% to 10%, for example, 0%, 0.1%, 1%, 2%, 4%, 6%, 8%, 10% or a range consisting of any two of these values.
[0058] In some embodiments, in the lithium transition metal oxide, the ratio of the molar amount of the Li element to the total molar amount of the T element and the M element is 0.5 to 1.1, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1 or a range consisting of any two of these values.
[0059] In some embodiments, the lithium transition metal oxide further includes a Na element, and the molar percentage of the Na element is 0.1% to 20%, based on the total molar amount of the T element and the M element in the lithium transition metal oxide, for example, 0.1%, 0.5%, 1%, 2%, 5%, 8%, 10%, 15%, 20% or a range consisting of any two of these values.
[0060] In some embodiments, the lithium transition metal oxide further includes an R element, and the R element includes at least one of F, Cl, Br, I or N. Based on the total molar amount of the T element and the M element in the lithium transition metal oxide, the molar percentage of the R element is 0.1% to 10%, for example, 0.1%, 0.5%, 1%, 2%, 5%, 8%, 10% or a range consisting of any two of these values.
[0061] In some embodiments, the lithium transition metal oxide has a layered crystal structure.
[0062] In some embodiments, the lithium transition metal oxide includes Li x1 Na x2 Ni y1 Mn y2 Co y3 M z1 O2±mR m, 0.5≤x1≤1.1, 0.001≤x2≤0.2, 0.3≤y1≤0.7, 0≤y2≤0.7, 0≤y3≤0.5, 0≤z1≤0.1, 0≤m≤0.1, wherein the R element includes at least one of F, Cl, Br, I or N.
[0063] In some embodiments, the X-ray diffraction pattern of the positive electrode material has diffraction peaks in the ranges of 16° to 20°, 34° to 38°, and 42° to 46°.
[0064] In a second aspect, the present application further provides an electrochemical device, which includes a positive electrode, wherein the positive electrode includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer includes the positive electrode material of the first aspect.
[0065] In some embodiments, the positive electrode active material layer also includes a conductive agent and a binder. In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride or vinylidene fluoride-hexafluoropropylene copolymer, etc. In some embodiments, the conductive agent includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers and mixtures thereof. In some embodiments, the carbon-based material is selected from carbon black, acetylene black, Ketjen black, carbon nanotubes, carbon fibers, graphene or any combination thereof. In some embodiments, the metal-based material is selected from metal powder or metal fiber. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0066] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.
[0067] The electrochemical device of the present application further includes a negative electrode, which includes a negative electrode active material layer and a negative electrode current collector.
[0068] In some embodiments, the negative electrode active material layer includes a negative electrode active material, a binder and optionally a conductive agent. In some embodiments, the negative electrode active material includes at least one of a carbon material or a silicon material. In some embodiments, the carbon material includes at least one of graphite, hard carbon or soft carbon. In some embodiments, the silicon material includes at least one of silicon, silicon oxide, silicon carbon compound or silicon alloy. In some embodiments, the binder includes at least one of polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, polyvinyl ether or styrene-butadiene rubber. In some embodiments, the conductive agent can use any conductive material as long as it does not cause chemical changes. In some embodiments, the conductive agent includes at least one of conductive carbon black, acetylene black, carbon nanotubes, Ketjen black, carbon fiber or graphene.
[0069] In some embodiments, the negative electrode current collector may be copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0070] In some embodiments, the electrochemical device further comprises an electrolyte. In some embodiments, the electrolyte comprises a lithium salt and a non-aqueous solvent. In some embodiments, the lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB and lithium difluoroborate. For example, the lithium salt may be selected from LiPF6. In some embodiments, the non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound or a combination thereof. The carbonate compound may be a chain carbonate compound, a cyclic carbonate compound or a combination thereof. Examples of the chain carbonate compounds are dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and a combination thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) and combinations thereof. Examples of the above-mentioned carboxylate compounds are methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, caprolactone and combinations thereof. Examples of the above-mentioned ether compounds are dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran and combinations thereof.
[0071] According to some embodiments of the present application, in the electrochemical device, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the embodiments of the present application are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed by a material that is stable to the electrolyte of the present application. For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected. A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The binder includes at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. The polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride or vinylidene fluoride-hexafluoropropylene copolymer.
[0072] According to some embodiments of the present application, the electrochemical device of the present application includes, but is not limited to: all kinds of primary batteries or secondary batteries. In some embodiments, the electrochemical device is a lithium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to: lithium metal secondary battery, lithium ion secondary battery, lithium polymer secondary battery or lithium ion polymer secondary battery.
[0073] In a third aspect, the electronic device of the present application may be any device using the electrochemical device of the second aspect of the present application.
[0074] In some embodiments, the electronic device includes, but is not limited to: laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries or lithium-ion capacitors, etc.
[0075] Examples and Comparative Examples
[0076] Hereinafter, the present application will be further described in detail with reference to examples and comparative examples. It will be understood that the present application is not limited to these examples.
[0077] 1. Preparation of positive electrode materials
[0078] Comparative Example 1
[0079] Step 1. In a 5L continuous reactor, nickel sulfate and manganese sulfate are mixed in an aqueous solution at a molar ratio of Ni:Mn=50:50 to prepare a 2M metal salt solution, and the solution is connected to the reactor. 3L of deionized water is added to the reactor and nitrogen is introduced at a rate of 2L / min to remove dissolved oxygen. Then, a certain amount of 3M NaOH solution is introduced into the reactor, and at the same time, the mixture is stirred evenly at 1200rpm at 60°C and the pH is adjusted to 12.0. Then, 2M metal salt solution, 3M NaOH solution and 10% NH4OH aqueous solution are gradually added at a rate of 100mL / h, 100mL / h and 8mL / h, respectively, and the reaction is fully reacted for 24h to obtain a dense structure of Ni 0.5 Mn 0.5 (OH)2 precursor;
[0080] Step 2: Prepare the dense structure Ni 0.5 Mn 0.5 The (OH)2 precursor and lithium carbonate were fully mixed in a ratio of (Ni+Mn):Li molar ratio = 1:1.02, reacted in an air atmosphere at 800°C for 20 hours, cooled to room temperature at a cooling rate of 10°C / min, and finally crushed and sieved to obtain the positive electrode material.
[0081] Comparative Example 2
[0082] The difference from Comparative Example 1 is:
[0083] Step 2: Prepare the dense structure Ni 0.5 Mn 0.5The (OH)2 precursor and sodium carbonate were fully mixed at a molar ratio of (Ni+Mn):Na=1:1.05, reacted in an air atmosphere at 800°C for 20h, cooled to room temperature at a cooling rate of 10°C / min, and finally crushed and sieved to obtain an intermediate product;
[0084] Step 3, the intermediate product and the lithium source (a mixture of lithium hydroxide and lithium nitrate in a molar ratio of 1:1) are mixed in a mass ratio of 1:10, the temperature is increased to 400°C at a heating rate of 10°C / min, and the temperature is maintained for 10 hours, and then the temperature is reduced to room temperature at a cooling rate of 50°C / min in a mixture of Ar and air (volume ratio of 1:1), the product is fully soaked and stirred in deionized water, and the positive electrode material is obtained by suction filtration, vacuum drying, crushing and sieving.
[0085] Comparative Example 3
[0086] Step 1, in a 5L continuous reactor, nickel sulfate and manganese sulfate are mixed in an aqueous solution at a molar ratio of Ni:Mn=50:50 to prepare a 2M metal salt solution, and connected to the reactor; in addition, nickel sulfate and manganese sulfate are mixed at a molar ratio of Ni:Mn=50:50 to prepare a 3M metal salt solution, and connected to the reactor; 3M NaOH solution and 10% NH4OH aqueous solution are prepared respectively, and connected to the reactor respectively; 3L deionized water is added to the reactor and nitrogen is introduced at a rate of 2L / min to remove dissolved oxygen, and then a certain amount of 3M NaOH solution is introduced into the reactor, and at the same time, the pH is adjusted to 12.0 while stirring uniformly at a speed of 1200rm at 60°C. Afterwards, 2M metal salt solution, 3M NaOH solution and 10% NH4OH aqueous solution are gradually added at a rate of 100mL / h, 100mL / h and 8mL / h, respectively. After the reaction of 2M metal salt solution was completed, 3M metal salt solution, 3M NaOH solution and 10% NH4OH aqueous solution were gradually added at a rate of 100mL / h, 140mL / h and 13mL / h respectively, and the reaction was fully carried out for 24h to obtain a Ni 0.5 Mn 0.5 (OH)2 precursor;
[0087] Step 2: Prepare the hollow ring structure Ni 0.5 Mn 0.5 The (OH)2 precursor and sodium carbonate were fully mixed in a ratio of (Ni+Mn):Na molar ratio = 1:1.05, reacted in an air atmosphere at 800°C for 20h, cooled to room temperature at a cooling rate of 10°C / min, and finally crushed and sieved to obtain the first product;
[0088] Step 3: Mix the first product with a lithium source (a mixture of lithium hydroxide and lithium nitrate in a molar ratio of 1:1) at a mass ratio of 1:10, heat to 400°C at a heating rate of 10°C / min, and keep the temperature constant for 10 hours. Then cool to room temperature at a cooling rate of 50°C / min in a mixture of Ar and air (volume ratio of 1:1); fully soak and stir the product in deionized water, and obtain the positive electrode material by suction filtration, vacuum drying, crushing, and sieving.
[0089] Example 1
[0090] Step 1, in a 5L continuous reactor, nickel sulfate and manganese sulfate are mixed in an aqueous solution at a molar ratio of Ni:Mn=50:50 to prepare a 2M metal salt solution, and connected to the reactor; in addition, nickel sulfate and manganese sulfate are mixed at a molar ratio of Ni:Mn=50:50 to prepare a 3M metal salt solution, and connected to the reactor; 3M NaOH solution and 10% NH4OH aqueous solution are prepared respectively, and connected to the reactor respectively; 3L deionized water is added to the reactor and nitrogen is introduced at a rate of 2L / min to remove dissolved oxygen, and then a certain amount of 3M NaOH solution is introduced into the reactor, and at the same time, the pH is adjusted to 12.0 while stirring uniformly at a speed of 1200rm at 60°C. Afterwards, 2M metal salt solution, 3M NaOH solution and 10% NH4OH aqueous solution are gradually added at a rate of 100mL / h, 100mL / h and 8mL / h, respectively. After the reaction of 2M metal salt solution was completed, 3M metal salt solution, 3M NaOH solution and 10% NH4OH aqueous solution were gradually added at a rate of 100mL / h, 150mL / h and 12mL / h respectively, and the reaction was fully carried out for 24h to obtain a Ni-ring hollow structure. 0.5 Mn 0.5 (OH)2 precursor;
[0091] Step 2: Prepare the hollow ring structure Ni 0.5 Mn 0.5 The (OH)2 precursor and sodium carbonate were fully mixed in a ratio of (Ni+Mn):Na molar ratio = 1:1.05, reacted in an air atmosphere at 800°C for 20h, cooled to room temperature at a cooling rate of 10°C / min, and finally crushed and sieved to obtain the first product;
[0092] Step 3: Mix the first product with a lithium source (a mixture of lithium hydroxide and lithium nitrate in a molar ratio of 1:1) at a mass ratio of 1:10, heat to 400°C at a heating rate of 10°C / min, and keep the temperature constant for 10 hours. Then cool to room temperature at a cooling rate of 50°C / min in a mixture of Ar and air (volume ratio of 1:1); fully soak and stir the product in deionized water, and obtain the positive electrode material by suction filtration, vacuum drying, crushing, and sieving.
[0093] Example 2-3
[0094] The difference from Example 1 is that the constant temperature time in step 3 is adjusted to 8 hours and 5.5 hours respectively.
[0095] Embodiment 4-15
[0096] The difference between Example 4, Example 7, Example 10 and Example 13 and Example 1 is that in step 2, calcium oxide or strontium hydroxide is mixed with the hollow ring structure Ni in different proportions. 0.5 Mn 0.5 The (OH)2 precursor and sodium carbonate are thoroughly mixed.
[0097] The difference between Example 5, Example 8, Example 11 and Example 14 and Example 2 is that in step 2, calcium oxide or strontium hydroxide is added to the hollow ring structure Ni in different proportions. 0.5 Mn 0.5 The (OH)2 precursor and sodium carbonate are thoroughly mixed.
[0098] The difference between Example 6, Example 9, Example 12 and Example 15 and Example 3 is that in step 2, calcium oxide or strontium hydroxide is added to the hollow ring structure Ni in different proportions. 0.5 Mn 0.5 The (OH)2 precursor and sodium carbonate are thoroughly mixed.
[0099] Table 1 shows the average diameter D of the positive electrode material particles, the length L of the pores, the width d of the pores, the porosity Vc1, the porosity Vc2, and the difference between Vc2 and Vc1 in Comparative Examples 1-3 and Examples 1-15.
[0100] Table 1
[0101]
[0102]
[0103] 2. Preparation of lithium-ion batteries:
[0104] (1) Preparation of lithium-ion button cells:
[0105] The binder polyvinylidene fluoride (PVDF), the conductive agent conductive carbon black (Super P) and the positive electrode material are mixed in a weight ratio of 1.5:1.5:97, added to N-methylpyrrolidone (NMP) and mixed evenly to prepare a positive electrode slurry with a solid content of 0.7. The mixed slurry is evenly coated on aluminum foil, and after drying, it is rolled to form the required electrode, wherein the electrode coating surface density is 14mg / cm 2, the positive electrode sheet is obtained after drying, and punched into a disc with a diameter of 14mm to prepare a single-sided positive electrode sheet. The separator is punched into a disc with a diameter of 18mm; the negative electrode used is a lithium metal sheet with a diameter of 18mm; LiPF6 is added to a solvent mixed with propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) (weight ratio 1:1:1) and mixed evenly to obtain an electrolyte, wherein the mass concentration of LiPF6 is 12.5% based on the mass of the electrolyte. The positive electrode sheet, separator, negative electrode sheet (lithium sheet), electrolyte, battery shell and other accessories are moved into the glove box (the water content must be less than 11ppm); the battery is assembled and the electrolyte is injected in the stacking order from bottom to top: negative electrode shell> flat gasket> metal lithium sheet + appropriate amount of electrolyte> a layer of separator + appropriate amount of electrolyte> positive electrode sheet + appropriate amount of electrolyte> flat gasket> shrapnel> positive electrode shell; packaged on a packaging machine to obtain a button battery.
[0106] (2) Preparation of lithium-ion soft-pack batteries
[0107] Preparation of positive electrode
[0108] The binder polyvinylidene fluoride (PVDF), the conductive agent conductive carbon black (Super P) and the positive electrode material are mixed in a weight ratio of 1.5:1.5:97, added to N-methylpyrrolidone (NMP) and mixed evenly to prepare a positive electrode slurry with a solid content of 0.7. The mixed positive electrode slurry is evenly coated on one side of the aluminum foil, and the above steps are repeated on the other side of the aluminum foil after drying to obtain a double-sided coated positive electrode sheet; after cold pressing, cutting, and welding the pole ears, the positive electrode is obtained.
[0109] Preparation of negative electrode
[0110] Artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose (CMC) were mixed with deionized water in a mass ratio of 96:2:2 and stirred evenly to obtain negative electrode slurry. The negative electrode slurry was evenly coated on one side of the copper foil, and after drying, the above steps were repeated on the other side of the copper foil to obtain a double-sided coated negative electrode sheet; after cold pressing, cutting and welding of the pole ears, the negative electrode was obtained.
[0111] Preparation of electrolyte
[0112] Under a dry argon environment, LiPF6 was added to a solvent mixed with propylene carbonate (PC), ethylene carbonate (EC) and diethyl carbonate (DEC) (weight ratio of 1:1:1), and the mixture was evenly mixed to obtain an electrolyte, wherein the mass concentration of LiPF6 based on the total weight of the electrolyte was 12.5%.
[0113] Preparation of isolation membrane
[0114] A polyethylene (PE) porous polymer film is used as the isolation membrane.
[0115] Preparation of Lithium-ion Soft-Pack Batteries
[0116] The positive electrode, separator, and negative electrode are stacked in order, with the separator placed between the positive and negative electrodes to isolate them, and then wound to obtain a bare cell. The bare cell is placed in an outer packaging aluminum-plastic film, and the electrolyte is injected and packaged. After the formation, degassing, and trimming processes, a lithium-ion soft-pack battery is obtained.
[0117] Test Method
[0118] 1. Test of porosity, average diameter D, hole length L and width d
[0119] The positive electrode sheet was cut longitudinally using ion polishing, and then a scanning electron microscope (instrument model: ZEISS SEM, acceleration voltage: 0.1KV to 30KV) was used to observe the morphology of the positive electrode material particles in the cross section of the positive electrode sheet and take microscopic photos. In the cross-sectional photo, the midpoint of the longest diameter of the positive electrode material particle was taken as the center, and the area surrounded by the first dividing point was determined as the first area, wherein the line from the center to any point on the surface of the positive electrode material particle in the cross section was the first connecting line, and the distance from the center to the first dividing point was 3 / 5 of the length of the first connecting line where the first dividing point was located, and the area outside the first area was the second area. The porosity of the first area and the porosity of the second area were counted using image processing software, and 20 positive electrode material particles were randomly selected, and the average of the porosity of the first area and the porosity of the second area was taken as the porosity Vc1 of the first area of the positive electrode material and the porosity Vc2 of the second area, and the average of the longest diameters was taken as the average diameter D of the positive electrode material. Among them, the porosity Vc = (total area of pores in a specific region / total area of the specific region) × 100%. At the same time, 20 holes were randomly selected from the cross-sectional photo of the positive electrode material, and the maximum length of the hole and the maximum width perpendicular to the maximum length were measured. The average value of the maximum length was taken as the length L of the hole, and the average value of the maximum width was taken as the width d of the hole.
[0120] 2.XRD test
[0121] The positive electrode material was tested by an X-ray powder diffractometer (instrument model: Bruker D8 ADVANCE, target material: Cu Kα; voltage and current: 40 KV / 40 mA, scanning angle range: 10° to 70°) to obtain an X-ray diffraction pattern of the positive electrode material.
[0122] 3.85℃ storage thickness expansion test
[0123] The lithium-ion soft-pack battery was charged to 4.35V at 0.5C at 25°C, and then charged to 0.05C at a constant voltage at 4.35V. The thickness of the lithium-ion battery was measured with a micrometer and recorded as H1. The lithium-ion battery was then placed in an oven at 85°C for 12 hours. After 12 hours, the thickness of the lithium-ion battery was measured with a micrometer and recorded as H2.
[0124] The thickness expansion ratio (%) of the lithium-ion battery after being stored at 85° C. for 12 hours = (H2 −H1) / H1×100%.
[0125] 4.45℃ Cycle Capacity Retention Test
[0126] The lithium-ion soft-pack battery was placed in a 45°C constant temperature box and allowed to stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature; the lithium-ion battery that reached a constant temperature was charged to 4.35V at a constant current of 1.5C at 45°C, and then charged to 0.02C at a constant voltage of 4.35V; it was allowed to stand for 5 minutes, and then discharged to 2.8V at a constant current of 4C, and allowed to stand for 5 minutes. The discharge capacity of this test was recorded as the first cycle discharge capacity; this charge and discharge cycle was repeated 300 times, and the discharge capacity of the 300th cycle of the test battery was recorded as the 300th cycle discharge capacity.
[0127] The capacity retention rate (%) of a lithium-ion battery after 300 cycles at 45° C. = 300th cycle discharge capacity / first cycle discharge capacity×100%.
[0128] 5.Q1 / Qt, dQ / dV test
[0129] Using an electrochemical workstation, the charge and discharge curve of the lithium-ion button battery in the voltage range of 2.8V to 4.5V was tested at 25°C; first, 0.1C constant current was charged to 4.5V, then 4.5V constant voltage was charged to a current of 0.02C; after standing for 5 minutes, 0.1C constant current was discharged to 2.8V, and then stood for 5 minutes; the discharge capacity in the voltage range of 4.2 to 4.5V was calculated to be Q1, and the discharge capacity in the voltage range of 2.8V to 4.5V was Qt. At the same time, according to the dQ / dV curve, the peak position of the first oxidation peak Vo1(V), the peak position of the first reduction peak Vr1(V), the peak position of the second oxidation peak Vo2, the peak position of the second reduction peak Vr2(V) and the absolute value of the first reduction peak dQ / dV were obtained.
[0130] 6. First cycle coulomb efficiency test
[0131] The lithium-ion soft-pack battery was charged to 4.35V at 0.2C at 25°C, then charged to 0.02C at 4.35V; left for 5 minutes, then discharged to 2.8V at 0.2C, and left for 5 minutes. The ratio of discharge capacity to charge capacity is the first cycle coulomb efficiency.
[0132] 7. Capacity retention rate after power-off cycle
[0133] Charge the button cell at 25°C at a constant current of 0.1C to 4.5V, then charge at a constant voltage of 4.5V to a current of 0.02C; let stand for 5 minutes, then discharge at a constant current of 0.1C to 2.8V, let stand for 5 minutes. Record the discharge capacity of the first cycle as C1. Repeat the above cycle 50 times. Record the discharge capacity of the 50th cycle as C50. The capacity retention rate after 50 cycles of charging = (C50 / C1) × 100%.
[0134] Test Results
[0135] Table 2
[0136]
[0137] By comparing the data of Examples 1-15 with those of Comparative Examples 1-3, it can be seen that by reasonably regulating the distribution of the pore structure inside the positive electrode material particles, 5%≤Vc2-Vc1≤30%, the capacity retention rate of the positive electrode material during the power cycle, the 85°C storage thickness expansion rate of the lithium-ion battery, the 45°C cycle capacity retention rate and other performances are significantly improved, indicating that limiting the size and distribution of the porosity of the positive electrode material within a reasonable range can not only ensure the transmission of electrons and ions, but also accommodate the volume change of the material, and can effectively reduce the effects of cold pressing of the pole piece and charge and discharge cycles on the stress between the polycrystalline particles of the positive electrode material, thereby improving the problem of particle cracks caused by cold pressing and cycling, and further improving the cycle performance and high temperature storage performance of the lithium-ion battery.
[0138] At the same time, by the attached Figure 1 It can be seen that in the cross-sectional SEM photo of the positive electrode material particles of Example 1 of the present application, the length direction of the hole is consistent with the radial direction of the cross section, and the holes are radially spaced. The holes arranged in the above manner can better disperse the stress during cold pressing and cycling, reduce the particle cracking phenomenon during cold pressing and cycling, and thus better improve the cycling performance and high temperature storage performance of lithium-ion batteries.
[0139] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A positive electrode material, wherein the cross section of the positive electrode material particle comprises a first region and a second region; in, Taking the midpoint of the longest diameter in the cross section as the center, a line connecting the center to any point on the surface of the positive electrode material particle in the cross section is a first line, the first line has a first dividing point, the distance from the center to the first dividing point is 3 / 5 of the length of the first line where the first dividing point is located, the first area is the area surrounded by the first dividing point; the second area is the area outside the first area in the cross section; The void ratio of the first region is Vc1, and the void ratio of the second region is Vc2, which satisfies: 5%≤Vc2-Vc1≤30%.
2. The positive electrode material according to claim 1, wherein The positive electrode material satisfies at least one of the following conditions (1) to (3): (1) 7% ≤ Vc2-Vc1 ≤ 18%; (2) 3% ≤ Vc1 ≤ 30%; (3) 10% ≤ Vc2 ≤ 35%.
3. The positive electrode material according to claim 1, wherein The second region includes a hole, and the hole satisfies at least one of the following conditions (1) to (4): (1) The length of the hole is L, L≤5 μm; (2) The width of the hole is d, d≤1.5 μm; (3) The length direction of the hole is consistent with the radial direction of the second region; (4) The holes are distributed radially at intervals.
4. The positive electrode material according to claim 1, wherein The positive electrode material and lithium metal are assembled into a button battery. When the button battery is charged and discharged at a current of 0.1C in a voltage range of 2.8V to 4.5V, the obtained capacity-voltage differential dQ / dV curve has a first oxidation peak and a first reduction peak in the range of 4.2V to 4.5V.
5. The positive electrode material according to claim 4, wherein The positive electrode material satisfies at least one of the following conditions (1) to (6): (1) Based on the mass of the positive electrode material, the peak height of the first oxidation peak is in the range of 2000 mAh / g / V to 4000 mAh / g / V; (2) Based on the mass of the positive electrode material, the absolute value of the peak height of the first reduction peak is in the range of 2000 mAh / g / V to 4000 mAh / g / V; (3) The peak voltage of the first oxidation peak is Vo1, the peak voltage of the first reduction peak is Vr1, and |Vo1-Vr1|≤0.2V; (4) The capacity-voltage differential dQ / dV curve has a second oxidation peak and a second reduction peak in the range of 3.6 V to 4.0 V, the peak voltage of the second oxidation peak is Vo2, the peak voltage of the second reduction peak is Vr2, and |Vo2-Vr2|≤0.3 V; (5) When the button battery is charged and discharged at a current of 0.1C in the voltage range of 2.8V to 4.5V, the discharge curve in the obtained voltage-capacity curve has a platform in the range of 4.2V to 4.5V; (6) When the button battery is charged and discharged at a current of 0.1C in the voltage range of 2.8V to 4.5V, the capacity of the discharge curve in the voltage-capacity curve obtained in the range of 4.2V to 4.5V is Q1, and the capacity of the discharge curve in the range of 2.8V to 4.5V is Qt, satisfying: 0.2≤Q1 / Qt≤0.
35.
6. The positive electrode material according to any one of claims 1 to 5, wherein The positive electrode material includes a lithium transition metal oxide, the lithium transition metal oxide includes a T element and an optional M element, the T element includes at least one of Ni, Co or Mn, and the M element includes at least one of K, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, B, Si, P, S, Sc, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge; the lithium transition metal oxide satisfies at least one of the following conditions (1) to (4): (1) Based on the total molar amount of T element in the lithium transition metal oxide, the molar percentage of Ni element is 30% to 70%; (2) based on the total molar amount of T element in the lithium transition metal oxide, the molar percentage of Mn element is less than or equal to 70%; and / or, based on the total molar amount of T element in the lithium transition metal oxide, the molar percentage of Co element is less than or equal to 50%; (3) Based on the total molar amount of the T element and the M element in the lithium transition metal oxide, the molar percentage of the T element is 90% to 100%, and the molar percentage of the M element is 0% to 10%; (4) In the lithium transition metal oxide, the ratio of the molar amount of the Li element to the total molar amount of the T element and the M element is 0.5 to 1.
1.
7. The positive electrode material according to claim 6, wherein The lithium transition metal oxide satisfies at least one of the following conditions (1) to (4): (1) The lithium transition metal oxide further comprises a Na element, and the molar percentage of the Na element is 0.1% to 20% based on the total molar amount of the T element and the M element in the lithium transition metal oxide; (2) The lithium transition metal oxide further comprises an R element, wherein the R element comprises at least one of F, Cl, Br, I or N, and the molar percentage of the R element is 0.1% to 10% based on the total molar amount of the T element and the M element in the lithium transition metal oxide; (3) The lithium transition metal oxide has a layered crystal structure; (4) The lithium transition metal oxide includes Li x1 Na x2 Ni y1 Mn y2 Co y3 M z1 O2±mR m , 0.5≤x1≤1.1, 0.001≤x2≤0.2, 0.3≤y1≤0.7, 0≤y2≤0.7, 0≤y3≤0.5, 0≤z1≤0.1, 0≤m≤0.1, wherein the R element includes at least one of F, Cl, Br, I or N.
8. The positive electrode material according to claim 1, wherein The X-ray diffraction spectrum of the positive electrode material has diffraction peaks in the ranges of 16° to 20°, 34° to 38°, and 42° to 46°. 9 . An electrochemical device comprising a positive electrode, the positive electrode comprising a positive electrode active material layer, the positive electrode active material layer comprising the positive electrode material according to claim 1 .
10. An electronic device comprising the electrochemical device according to claim 9.
Citation Information
Patent Citations
Nickel-based active material for lithium secondary battery, method of preparing nickel-based active material, and lithium secondary battery including positive electrode including nickel-based active material
CN108123119A
Positive electrode active material, electrochemical device and electronic device
CN111370681A
Positive electrode material, and electrochemical device and electronic device including positive electrode material
CN116325219A
Positive active material for nonaqueous electrolyte secondary battery, method of manufacturing the positive active material, electrode for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery and method of manufacturing the secondary battery
US20130313471A1
Nickel-based active material for lithium secondary battery, method of preparing the same, and lithium secondary battery including positive electrode including the nickel-based active material
US20180159128A1
Cited By
Positive electrode material, electrochemical apparatus and electronic apparatus
WO2026156537A1
